Clinical opthalmology a systematic approach - Kanski, Jack J. (Elsevier/Saunders, 2011)
Suitable for rapid reference and efficient, effective recall, this title offers evolving practice in the diagnosis and management of ophthalmic disorders, using a succinct format that facilitates comprehension for trainees and practitioners.